Imagined communities : reflection on the origin and spred of nationalism - Anderson, Benedict (Verso, 2006)
The full magnitude of Benedict Anderson’s intellectual achievement is still being appreciated and debated. Imagined Communities remains the most influential book on the origins of nationalism, filling the vacuum that previously existed in the traditions of Western thought. Cited more often than any other single English-language work in the human sciences, it is read around the world in more than thirty translations.